PENINGKATAN KOMPETENSI PEDAGOGIK GURU TK SANTA LUSIA MEDAN DALAM MEMBUAT MEDIA PEMBELAJARAN ERA 5.0 MELALUI SUPERVISI AKADEMIK - Saloma; Saut Purba; Irsan Rangkuti (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2023)
This study aims to see the improvement of pedagogical competence of Santa Lusia Medan kindergarten teachers in making era 5.0 learning media through academic supervision. This research uses descriptive qualitative methods. The results showed that teachers are willing and able to keep up with developments in the world of teaching where with the development of the times, especially in the 5.0 era, learning media that rely more on technology is also developing. The teachers felt enthusiastic about the material presented about the 5.0 era learning media in the form of power points that have images and sounds which are certainly very interesting for early childhood to strengthen their numeracy literacy reading literacy. In this case, teachers' skills have also increased where they are willing and able to design this 5.0 era learning media in teaching activities in the classroom.